2020
DOI: 10.1021/acs.langmuir.0c02434
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CO2/CH4 Separation in Pristine and Defective 2D MOF CuBDC Nanosheets via Nonequilibrium Molecular Dynamics

Abstract: The separation of CO 2 /CH 4 gas mixtures is a key challenge for the energy sector and is essential for the efficient upgrading of natural gas and biogas. A new emerging field, that of metal−organic framework nanosheets (MONs), has shown the potential to outperform conventional separation methods and bulk metal−organic frameworks (MOFs). In this work, we model the CO 2 /CH 4 separation in both defect-free and defective 2D CuBDC nanosheets and compare their performance with the bulk CuBDC MOF and experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The organic moieties are commonly aromatic polycarboxylates or multinitrogen organic compounds. As a consequence, MOFs are highly tunable with great potential for gas storage and separation, energy storage, catalysis, and detection of biomarkers . Among them, lanthanide metal–organic framework (Ln-MOFs), as a promising fluorescent material, have attracted more and more attention due to their luminescence properties such as a large Stokes shift, high quantum yields, and long luminescence lifetimes .…”
Section: Introductionmentioning
confidence: 99%
“…The organic moieties are commonly aromatic polycarboxylates or multinitrogen organic compounds. As a consequence, MOFs are highly tunable with great potential for gas storage and separation, energy storage, catalysis, and detection of biomarkers . Among them, lanthanide metal–organic framework (Ln-MOFs), as a promising fluorescent material, have attracted more and more attention due to their luminescence properties such as a large Stokes shift, high quantum yields, and long luminescence lifetimes .…”
Section: Introductionmentioning
confidence: 99%
“…CuBDC nanosheets and compared their performance with the bulk CuBDC MOF. 104 Studies revealed that separation mechanism is basically a pore blocking effect. Most of the adsorption sites were occupied by CO2 molecules that can show strong interaction with the framework atoms and thus possess a lower velocity through the MON, hence limiting the CH4 molecule permeability through the nanosheet.…”
Section: Gas Separationmentioning
confidence: 99%
“…Compared with traditional high-energy materials, the design of novel high-energy explosives is based on insights into multiple subjects, including synthetic methodology, crystal engineering, and computational science. Crystal design of high-energy materials is also an important method. In nature, molecules with a layer-by-layer structure are widespread. More importantly, highly ordered structures formed in this way often exhibit fascinating properties, which have enlightened researchers to advance in-depth research on this system. …”
Section: Introductionmentioning
confidence: 99%